2020
DOI: 10.1007/s00198-019-05252-8
|View full text |Cite
|
Sign up to set email alerts
|

Hip protectors are cost-effective in the prevention of hip fractures in patients with high fracture risk

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
(220 reference statements)
0
17
0
Order By: Relevance
“…A systematic review undertaken by de Bot et al concluded that the use of hip protectors in an elderly population at high risk for hip fractures, such as nursing home residents or patients in a geriatric ward in a hospital, was a cost-effective approach to preventing hip fractures [ 9 ]. Another study performed by Singh et al found that the use of hip protectors was a more cost-effective method compared to no treatment or the use of calcium and vitamin D supplements [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review undertaken by de Bot et al concluded that the use of hip protectors in an elderly population at high risk for hip fractures, such as nursing home residents or patients in a geriatric ward in a hospital, was a cost-effective approach to preventing hip fractures [ 9 ]. Another study performed by Singh et al found that the use of hip protectors was a more cost-effective method compared to no treatment or the use of calcium and vitamin D supplements [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Approximately 30,000 hip fractures occur each year in Canada 3 and more than 90% of hip fractures are attributable to falls. 4 There are a number of risk factors associated with hip fractures such as female gender, older age, low cognitive function, and previous spine or hip fracture. 4 There are several interventions that aim to reduce the number of hip fractures in older adults.…”
Section: Context and Policy Issuesmentioning
confidence: 99%
“…4 There are a number of risk factors associated with hip fractures such as female gender, older age, low cognitive function, and previous spine or hip fracture. 4 There are several interventions that aim to reduce the number of hip fractures in older adults. These include regular exercise, pharmacological treatments (e.g., calcium, vitamin D), and the use of hip protectors.…”
Section: Context and Policy Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intertrochanteric fractures are common injuries in elderly, with estimated prevalence of intertrochanteric fractures greater than 150,000 cases in the USA annually [ 1 , 2 ]. Patients with intertrochanteric fractures always have a history of falls or bone disease, which might be due to a low-energy mechanism including fall from standing [ 3 , 4 ]. Further, the typical clinical manifestations include pain and difficulty walking.…”
Section: Introductionmentioning
confidence: 99%